THYROID NODULES SEGMENTATION USING DEEP LEARNING APPROACHES - B.S, SRUTHY; MURUGANANTHAM, S. (International Journal of Psychosocial Rehabilitation, 2019)
ultrasound is an clear procedure that interpret the internal structure of an organ.It is an unique method that provides most important,rapid and clear evaluation in everymeans.Due to the presence of an unwanted noise in an image it is an challenging task to segementing an image.So in this work we introduce an effective method to segment the image and findout the problem more clear.ultrasound image is the most common method that used nowdays because of its imaging technique and the visibility of the internal structure of an organ.The medical reports usually offer quantative analysis of data due to the changes in prior study.Henceforth it is important to give information about an image based upon its size and shape.Image segmentation is the most common tools that used in processing the medical image.Different algorithms that are used to segment the ultrasound image and for further classification.